Rapid nanopore sequencing as a key diagnostic tool in adrenal histoplasmosis after a year of uncertainty - Zainulabid, Ummu Afeera; Cheong, Xiong Khee; Kori, Najma; Periyasamy, Petrick; Abdul Muien, Muhammad Zahid; Musily, Raniza; Mohamed Rose, Isa; Zaidan, Noor; Ismail, Nordiana; Neoh, Hui-min; Han Min, Gan (Elsevier, 2025)
Histoplasmosis, caused by Histoplasma capsulatum, exhibits a broad clinical spectrum, ranging from asymptomatic pulmonary infections to disseminated disease. Atypical presentations, such as isolated adrenal involvement, can pose significant diagnostic challenges, underscoring the need for rapid and accurate diagnostic tools. This report highlights a challenging case of adrenal histoplasmosis diagnosed through ampli- con-based Nanopore sequencing after a year of diagnostic uncertainty.